Purple tea catechins exhibit high antiproliferative activity and synergism with cisplatin against the triple-negative breast cancer cell line 4T1 - Ndacyayisenga, Joseph; Maina, Esther N.; Ngeny, Lilian C.; Wamunyokoli, Fred; Tolo, Festus M. (Archives of Biological Sciences, 2023)
Paper Description: Tea catechins are reported to have health benefits, that include free radical scavenging and anti-cancer activities. Their content in different tea clones and the effects of their combination with chemotherapy drugs are not well understood. The concentrations of catechins in purple TRFK306 and BB35 tea clones from Rwanda and Kenya were determined, and the antiproliferative activity and synergism of the catechin extracts with cisplatin on the triple-negative breast cancer (TNBC) cell line (4T1) were evaluated. Purple tea catechin extracts showed higher anti-proliferative activity and synergism with cisplatin. Purple tea catechins reduced doses of cisplatin up to 3.7-fold, lowering cisplatin toxicity. Abstract: The objectives of this study were the selection of the best tea clones with high catechin content among the known tea clones in Rwanda and Kenya, the examination of their antiproliferative effects on the triple-negative breast cancer (TNBC) cell line (4T1), and an evaluation of their combination index with cisplatin. The quantification of catechin contents in 14 different tea clones and 5 different processed teas was performed by high-performance liquid chromatography (HPLC). A comparative study of antiproliferative activities of catechin extracts from purple, TRFK306, and BB35 tea clones on the TNBC cell line (4T1) was undertaken, and their combination index (CI) with cisplatin and the dose reduction index (DRI) were determined. The catechin extract from BB35 had the highest concentration of total catechins (817.81±24.2 mg/g DW). After 72 h, the catechin extracts from TRFK306 showed a high IC50 of 68.68±3.30 µg/mL. The catechin extracts from TRFK306 showed the best synergism with cisplatin (CI=0.59), and they reduced the doses of cisplatin with the highest DRI=3.74493. Catechin extracts from purple tea showed higher antiproliferative activity and synergism with cisplatin against the TNBC cell line.